1993
DOI: 10.1111/j.1600-0609.1993.tb00638.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic dosing in prophylactic treatment of hemophilia A

Abstract: The aim of this study was to investigate individual pharmacokinetics as a tool for dosing of factor VIII (FVIII) in severe hemophilia A. It is assumed that effective prophylaxis against bleedings is maintained if the plasma FVIII:C activity is kept above 1 U/dl, and the present study is based on this assumption. A current standard dosage regimen for FVIII is 25–40 U/kg up to three times weekly. However, there is considerable individual variation in the pharmacokinetics of FVIII:C. Individual pharmacokinetic da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 111 publications
(65 citation statements)
references
References 13 publications
2
63
0
Order By: Relevance
“…Comparisons between the methodologically most robust studies on either species indicate that the average CL of recombinant FIX is twice as high as that of pdFIX [10]. This difference is confirmed in cross-over comparisons [37,38] [5,10,36]. The difference in CL between rFIX and pdFIX appears to be greater and more consistent between studies, than the difference in half-life, which demonstrate that the comparison cannot be based on only a single PK parameter.…”
Section: Pharmacokinetic Implications Of Dosingsupporting
confidence: 51%
See 3 more Smart Citations
“…Comparisons between the methodologically most robust studies on either species indicate that the average CL of recombinant FIX is twice as high as that of pdFIX [10]. This difference is confirmed in cross-over comparisons [37,38] [5,10,36]. The difference in CL between rFIX and pdFIX appears to be greater and more consistent between studies, than the difference in half-life, which demonstrate that the comparison cannot be based on only a single PK parameter.…”
Section: Pharmacokinetic Implications Of Dosingsupporting
confidence: 51%
“…Initially, simulations demonstrated the potential for more costeffective dosing [5]. Subsequently, a study on 21 patients with severe haemophilia A showed that prophylaxis aimed at targeting a trough level decided by the clinician, based on PK data (based on seven blood samples over 48 h), compared to standard dosing, resulted in a higher mean trough level (2.2 vs. 0.9 IU dL )1…”
Section: Pharmacokinetic Implications Of Dosingmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides these dosing schedules, pharmacokinetic modelling is sometimes used to calculate doses based on trough FVIII levels [6]. Indeed, it was shown that by increasing dosing frequency from three times per week to once per day, in line with maintained trough levels of FVIII, overall dosing requirements were reduced by 87% (from 6000 to 770 IU week )1 ) [6]. However, trough levels of FVIII are not the only important predictor of dosing requirements, and daily dosing is inconvenient for patients.…”
Section: Dosing Schedulesmentioning
confidence: 99%